Impact of Resident-Led Small-Group Learning Sessions on Preclinical Students' Perceptions of Ophthalmology - Sorab, Priya; Benza, Andrew R.; Patterson, Ian T.; Kelly, Lisa D. (Journal of Academic Ophthalmology, 2021)
Introduction Resident physicians have a significant role in the education of medical students, and limited research has demonstrated that positive interactions with residents are linked with enhanced students’ perceptions of a specialty. Minimal research on residents as teachers has been done in ophthalmology, and no research has examined the impact of residents as teachers on the perceptions of preclinical students. This is an important area of interest because ophthalmology conducts an early match. The competitiveness of the field increases the importance of early involvement in research and clinical activities. This study aimed to assess the role of a resident-led workshops as a vehicle for exposing preclinical students to ophthalmology.Methods A 2-hour workshop on the Ophthalmology Clinical Skills was held at the University of Cincinnati College of Medicine in November 2018. The workshop was conducted by seven ophthalmology residents, and the learners were 15 first-year and 11 second-year medical students. The workshop format consisted of a 30-minute introductory lecture on the field of ophthalmology, followed by a 60-minute small-group clinical skills’ session focusing on direct ophthalmoscopy and slit lamp examination. Preworkshop and postworkshop surveys were administered to the medical students, and Student’s paired sample t-test was used to assess the differences in responses before and after the workshop.Results Students’ average interest in ophthalmology rose (p = 0.049) as did their likeliness to approach a resident for career advice (p = 4.65 × 10−6) and their likeliness to attend the Secrets of the Match Lunch talk, a yearly talk held by a student matched into ophthalmology (p = 0.002).Conclusion These results suggest that resident intervention can have a positive impact on preclinical students’ perceptions of ophthalmology and may be a good educational strategy to foster their positive attitudes toward the field.
Keywords: ophthalmology; student; workshop; perceptions